Cut-off value of coronary flow velocity reserve obtained by transthoracic Doppler echocardiography during intravenous infusion of dobutamine for diagnosis of functional significant myocardial bridging. (14th October 2021) - Aleksandric, S; Djordjevic-Dikic, A; Tesic, M; Giga, V; Dobric, M; Banovic, M; Boskovic, N; Juricic, S; Vukcevic, V; Tomasevic, M; Stojkovic, S; Orlic, D; et al.
Abstract: Background: Recent studies showed that coronary flow velocity reserve (CFVR) measurement by transthoracic Doppler echocardiography (TTDE) during inotropic stimulation with dobutamine (DOB), in comparison to vasodilation with adenosine, provides more reliable functional evaluation of myocardial bridging (MB). However, the adequate cut-off value of CFVR during DOB for diagnosing functional significant MB has not been fully established. Purpose: The purpose of the study was to evaluate the adequate cut-off value of TTDE- CFVR during DOB for diagnosis of functional significant MB. Methods: This prospective study included 79 patients (54 males, mean age 55±10 years) with angiographic evidence of isolated MB on the left anterior descending artery (LAD) and systolic compression ≥50% diameter stenosis. Exercise stress-echocardiography test (ExSE) and TTDE-CFVR in the distal segment of LAD during DOB infusion (DOB: 10–40μg/kg/min) were performed in all patients. Percent diameter stenosis (DS) of MB at end-systole and end-diastole were analyzed using quantitative coronary angiography. Results: Exercise-SE was positive for myocardial ischemia in 22/79 (28%). CFVR during peak DOB was significantly lower in SE-positive group in comparison to SE-negative group (1.94±0.16 vs. 2.78±0.53, p<0.001). ROC analysis identifies the optimal CFVR during peak DOB cut-off value <2.1 (AUC 0.985, 95% CI: 0.965–1.000, p<0.001), with a sensitivity of 96% and specificity of 95%, positive predictive value of 88%, and negative predictive value of 98%, for identifying functionally significant MB associated with stress-induced myocardial ischemia. The categorical agreement between TTDE-CFVR at peak DOB and ExSE was high (kappa value = 0.877, p<0.001). Multivariate logistic regression analysis showed that percent DS at end-diastole was the only independent predictor of ischemic CFVR value <2.1 (OR: 1.136, 95% CI: 1.045–1.235, p=0.003). Conclusion: A cut-off value <2.1 of CFVR during DOB infusion obtained by TTDE may adequate discriminate functional significant MB that induce myocardial ischemia which is caused by an incomplete diastolic MB-decompression. FUNDunding Acknowledgement: Type of funding sources: None.